Srī 108 niramala sritāwatam̆sa brahma widuttama wiraktātamā paṇḍita Hari Siṅgha mahārāja jī kā jīwana caritra - Guraditta Siṅgha, Sādhū (SAMP early 20th-century Indian books project, 1917)
Biography of Paṇḍita Harī Siṅgha, Sikh religious leader.